Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1136/jech.50.4.415
|View full text |Cite
|
Sign up to set email alerts
|

Health and social precursors of unemployment in young men in Great Britain.

Abstract: Objective -To identify health and socioeconomic factors in childhood that are precursors of unemployment in early adult life and to examine the hypothesis that young men who become unemployed are more likely to have accumulated risks to health during childhood. Design -Longitudinal birth cohort study. The amount of unemployment experienced in early adult life up to age 32 years was the outcome measure used. Exposure measures to indicate vulnerability to future ill health were: height at age 7 years and the Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
76
1
5

Year Published

1997
1997
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(83 citation statements)
references
References 35 publications
(16 reference statements)
1
76
1
5
Order By: Relevance
“…Findings from a longitudinal study showed that women who came from manual social class families and held non-manual social class occupations in adulthood (at 36 years) tended significantly to show the prevalence of low obesity, as in the class they had joined, compared with the class they had left [77]. Unemployment is also commonly found to be associated with ill health [79][80][81] and premature death [82], and a life history approach to this subject shows the importance of pre-existing vulnerability [83]. Longitudinal studies have shown that unemployment is a greater risk for young adults from less favourable family circumstances, with low or no educational attainment, and with early signs of vulnerability to ill health in adulthood [7,83].…”
Section: Age Related Social Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from a longitudinal study showed that women who came from manual social class families and held non-manual social class occupations in adulthood (at 36 years) tended significantly to show the prevalence of low obesity, as in the class they had joined, compared with the class they had left [77]. Unemployment is also commonly found to be associated with ill health [79][80][81] and premature death [82], and a life history approach to this subject shows the importance of pre-existing vulnerability [83]. Longitudinal studies have shown that unemployment is a greater risk for young adults from less favourable family circumstances, with low or no educational attainment, and with early signs of vulnerability to ill health in adulthood [7,83].…”
Section: Age Related Social Factorsmentioning
confidence: 99%
“…Unemployment is also commonly found to be associated with ill health [79][80][81] and premature death [82], and a life history approach to this subject shows the importance of pre-existing vulnerability [83]. Longitudinal studies have shown that unemployment is a greater risk for young adults from less favourable family circumstances, with low or no educational attainment, and with early signs of vulnerability to ill health in adulthood [7,83]. Experience of divorce and separation is associated with raised risk of self-reported ill health [75] and with psychiatric morbidity [80], but little work has been reported on its association with physical health.…”
Section: Age Related Social Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, selection, where background and other personal characteristics, place persons simultaneously at higher risk for both unemployment and poor mental health (7,(15)(16)(17)(18)(19), might also explain the association.…”
mentioning
confidence: 99%
“…À noter que c'est bien la condition sociale représentée par le chômage qui est en cause et non l'inactivité professionnelle en soi, puisque l'augmentation du risque cardiovasculaire et la surmortalité ne se retrouvent pas chez les personnes volontairement inactives (essentiellement des femmes s'occupant d'enfants en bas âge), ou chez les retraités. L'extrapolation de la surmortalité observée dans cette de chômage, ces dernières pouvant être considérées, au même titre que les problèmes de santé, comme des événements faisant partie d'un parcours de vie globalement défavorable [28][29][30]. Il s'agit donc de phénomènes exerçant des effets réciproques les uns sur les autres et qui dépendent d'un contexte social plus large pouvant influencer leur survenue.…”
Section: Quelques Données Françaisesunclassified